Analisis Faktor Determinan Yang Mempengaruhi Profesionalitas Guru Bidang Studi Ilmu Sosial Di Kota Parepare - pabubung, Afrilya liliani; Rakib, Muhammad; Rahmatullah, Rahmatullah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
This study aims to study educational background, teaching experience, training (education and training), and facilities on the motivation teachers, to find out their educational background, teaching experience, training (training), facilities and infrastructure, motivation of teachers towards the professionalism of teachers and to understand the educational background, teaching experience, training (training), and infrastructure for teacher professionalism through social science teachers in the Municipality of Parepare.This research is quantitative research, a type of correlational research. The data obtained were analyzed by two types of statistics, namely descriptive statistics and inferential statistics: Data Normality Test and Hypothesis Test.The results showed that: (i) there was a direct significant influence, teaching experience, training (training), and infrastructure directly related to the motivation of teachers Parepare City, (ii) educational background, teaching experience, training, facilities and infrastructure, and direct teacher motivation on the professionalism of teachers in Parepare City, (iii) educational background, teaching experience, training (training), and indirect infrastructure facilities for teacher professionalism through social science teachers in Parepare CityÂ